2022
DOI: 10.1186/s13054-022-04098-7
|View full text |Cite
|
Sign up to set email alerts
|

Right dose, right now: bedside, real-time, data-driven, and personalised antibiotic dosing in critically ill patients with sepsis or septic shock—a two-centre randomised clinical trial

Abstract: Background Adequate antibiotic dosing may improve outcomes in critically ill patients but is challenging due to altered and variable pharmacokinetics. To address this challenge, AutoKinetics was developed, a decision support system for bedside, real-time, data-driven and personalised antibiotic dosing. This study evaluates the feasibility, safety and efficacy of its clinical implementation. Methods In this two-centre randomised clinical trial, crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…No benefit in terms of shortening the length of stay was observed, while target attainment in both MIDP and control groups was similar [ 139 ]. In a two-center Dutch trial, the adaptive dosing of four antibiotics including meropenem and ceftriaxone in septic patients did not lead to the better target attainment of these beta-lactams nor did it improve any clinical outcome [ 140 ]. While the effectiveness of the TDM guided approach to beta-lactam prescription has not been proven, it may be beneficial in certain subgroups of critically ill patients.…”
Section: Therapeutic Drug Monitoring Of Beta-lactam Antibioticsmentioning
confidence: 99%
“…No benefit in terms of shortening the length of stay was observed, while target attainment in both MIDP and control groups was similar [ 139 ]. In a two-center Dutch trial, the adaptive dosing of four antibiotics including meropenem and ceftriaxone in septic patients did not lead to the better target attainment of these beta-lactams nor did it improve any clinical outcome [ 140 ]. While the effectiveness of the TDM guided approach to beta-lactam prescription has not been proven, it may be beneficial in certain subgroups of critically ill patients.…”
Section: Therapeutic Drug Monitoring Of Beta-lactam Antibioticsmentioning
confidence: 99%
“…The selection of these factors was mostly based on our clinical experience and the literature. [19,20]…”
Section: Queue Informationmentioning
confidence: 99%
“…AI utilization in critical care primarily encompasses disease diagnosis, prediction of disease progression (clinical deterioration), and characterization of specific disease phenotypes or endotypes, [3] such as those found in sepsis, [14] septic shock, [15,16] and acute respiratory distress syndrome. [17] For example, in a large multicenter database, authors [18] compared various techniques for detecting clinical deterioration on wards and found that an AI expert algorithm was developed [19] to predict sepsis early.…”
Section: Literature Reviews Of Ai In Icusmentioning
confidence: 99%